Wali Dalam Pandangan Jawa - Qomari Qomari (Gelar : Jurnal Seni Budaya, 2007)
The background of this research was the fact that wali (the saint of Islam)  was a problem that had long existed in the history of Islam. The problem often  brought diffmnt opinions and disputes in the Moslems circle, and even ended in  conflict between Moslems. The cause was that wali was not onlY as the type and  substance of a good knowledge of Tr1ligion but it could also lead to superstition which  might mislead the Moslims.The modern lift provided many facilities in one hand, and made some people  fmstrated on the other hand so that some people tended to find an alternative way 10  give their peaceful life back.The problems discussed wm :1.     How the opinion of Javanese satiety on wali was.2.     Why the socie(y had that kind of opinion.3.How the opinion was seen from Islam point of view (tasawuf/ mysticism)  The answers to the problems uer« expected to be able to broaden our horizon andto Tr1vise the false opinion on wali.       This research takes the form of literary study and the tasawuf (IJ/am  mysticism) and historical approach was used. The data was collected by means of  documentation and interviews, and an analYtic descriptive analYsis was used.The Tr1sults of the researdi showed that:1.      The socie(y had a positive opinion on wali due to the wisdom of wali when they  spread Islam in Java.2.      The social condition and background in the past had a gTr1at influence on the  opinion of the socie(y on wali.3.      The opinion of the socie(y was parallel to and on the basis of wali.4.      The development of the opinion of Javanese socie(y on the problem showed tbat  the social background and way of thinking had a great influence on the social  way of thinking in the past.Keyword: Wali, Tasawuf, society